Anemia in older adults as a geriatric syndrome: A review. Issue 7 (3rd June 2021) - Katsumi, Akira; Abe, Akihiro; Tamura, Shogo; Matsushita, Tadashi
Abstract : Anemia, a frequently occurring condition in older patients, has no standard definition; however, in most studies, it is defined as hemoglobin level <12 and <13 g/dL in women and men, respectively. Approximately 10% of older adults living in the community have anemia. The prevalence of anemia is significantly correlated with advanced age and male sex. Anemia is associated with falls, frailty and other negative outcomes, including early mortality. However, there remains little consensus regarding whether anemia treatment favorably affects these adverse outcomes. Therefore, this article reviews the prevalence of anemia, and provides updates on its common causes and treatments in older adults. While excluding well‐established hematopoietic diseases, the etiology of anemia in older adults has been grouped into four categories: (i) nutritional deficiency; (ii) inflammation; (iii) clonal hematopoiesis; and (iv) "unexplained anemia, " when there is no clear mechanism to account for the anemia. Recently, clonal leukocytes were detected in a considerable number of older individuals. The number of somatic mutations in blood leukocytes increases with age; however, single mutations of DNMT3A, TET2 and ASXL1 are not correlated with the presence of unexplained anemia in older adults. With an increased understanding of anemia etiology and the availability of innovative anti‐anemic drugs, future studies that evaluate the causes and benefits of treatment are required. Geriatr Gerontol Int 2021; 21: 549–554 .